2015
DOI: 10.1093/mnras/stv1859
|View full text |Cite
|
Sign up to set email alerts
|

Astrophysical hydrodynamics with a high-order discontinuous Galerkin scheme and adaptive mesh refinement

Abstract: Solving the Euler equations of ideal hydrodynamics as accurately and efficiently as possible is a key requirement in many astrophysical simulations. It is therefore important to continuously advance the numerical methods implemented in current astrophysical codes, especially also in light of evolving computer technology, which favours certain computational approaches over others. Here we introduce the new adaptive mesh refinement (AMR) code TENET, which employs a high order discontinuous Galerkin (DG) scheme f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
75
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(88 citation statements)
references
References 35 publications
(42 reference statements)
2
75
0
Order By: Relevance
“…These new schemes are quite numerical complex and, in some cases, their space discretization does not seem to be optimal as required by forthcoming parallel computing systems consisting of several million cores (Schaal et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…These new schemes are quite numerical complex and, in some cases, their space discretization does not seem to be optimal as required by forthcoming parallel computing systems consisting of several million cores (Schaal et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In the context of decaying isothermal magnetized supersonic turbulence, the code comparison study of Kritsuk et al (2011) has shown that higher-order codes provide a larger turbulence spectral bandwidth and increased effective Reynolds number compared to second-order schemes. Even at second order, recent studies by Mocz et al (2014) and Schaal et al (2015) show that DG methods demonstrate overall superior accuracy compared to finite volume methods, in particular due to lower advection errors and reduced angular momentum diffusion. Beyond second order, Schaal et al (2015) find that, on smooth problems at least, increasing the DG order reduces advection errors, and decreases the total time-to-solution for a given target accuracy.…”
mentioning
confidence: 99%
“…Even at second order, recent studies by Mocz et al (2014) and Schaal et al (2015) show that DG methods demonstrate overall superior accuracy compared to finite volume methods, in particular due to lower advection errors and reduced angular momentum diffusion. Beyond second order, Schaal et al (2015) find that, on smooth problems at least, increasing the DG order reduces advection errors, and decreases the total time-to-solution for a given target accuracy.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We also implement a bounded version of this limiter in the spirit of and Schaal et al (2015), where the central difference slope is first evaluated against a threshold parameter before applying the minmod operator…”
Section: Slope Limitingmentioning
confidence: 99%